Shiitake Mushroom: A Tool of Medicine (Bangladesh Journal of Medical Biochemistry, 2013)
Medicinal mushrooms have an established history of use in traditional oriental therapies. Contemporary research has validated and documented much of the ancient knowledge. Over the last three decades, the interdisciplinary fields of science that study medicinal mushrooms has sprung up and has increasingly demonstrated the potent and unique properties of compounds extracted from a range of species. Currently, the field is being developed into a very fruitful area. Modern clinical practice in Japan, China, Korea and other Asian countries rely on mushroom-derived preparations.Mushrooms have been studied for nutritional and medical purposes for its various potential anti-tumoral and immunomodulatory componests like polysaccharides that have been identified. For medical purposes, mushrooms have been consumed to prevent cancer and cardiac diseases, to improve blood circulation and to reduce blood cholesterol level. Some of these mushrooms have also been used for the treatment of physical and emotional stress, osteoporosis, gastric ulcers and chronic hepatitis, for the improvement of the quality of life of patients with diabetes and especially for the stimulation of immunity.Shiitake has a history of medicinal uses. The mushroom is used as anticarcinogenic, antiinflammatory, antioxidant, antifungal, antibacterial, antiviral as well as antithrombotic in cardiovascular disorders. This article has been written to throw some light on Shiitake mushroom which has many nutritional values. Many Shiitake preparations came in market containing the active ingredients which can replace many other marketed synthetic medicines and may prove to have promising results with fewer side effects. DOI: http://dx.doi.org/10.3329/bjmb.v5i1.13428 Bangladesh J Med Biochem 2012; 5(1): 24-32